2007
DOI: 10.12968/ijpn.2007.13.9.27416
|View full text |Cite
|
Sign up to set email alerts
|

Macmillan nurse facilitators: establishing a palliative resource nurse network in primary care

Abstract: The establishment of a palliative resource network within primary care has been successful. It has provided an effective and efficient means of disseminating information across a large workforce and extensive geographical area. The development of a clear structured model benefits both the PRNs and the organisation by providing clear expectations of the role while offering a framework for professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The resource nurse is also supposed to work with system improvements related to routines, procedures and pathways, in addition to advising and guiding colleagues, disseminating new knowledge and initiating re ection (8). Parallel terms for the resource nurse in the Norwegian context are, in the international literature, the palliative resource nurse (10), link nurse (11) or palliative care champion (12).…”
Section: Introductionmentioning
confidence: 99%
“…The resource nurse is also supposed to work with system improvements related to routines, procedures and pathways, in addition to advising and guiding colleagues, disseminating new knowledge and initiating re ection (8). Parallel terms for the resource nurse in the Norwegian context are, in the international literature, the palliative resource nurse (10), link nurse (11) or palliative care champion (12).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept we previously studied the impact of a palliative care nurse champions program on the quality of dying in the hospital, as experienced by bereaved relatives [27,28]. We hypothesized that similar to nurse champions in other fields, palliative care nurse champions may contribute to better quality of palliative care by improving the recognition of palliative care needs, the communication with patients and relatives, and the care delivered to both [14,[29][30][31][32]. However, in our study bereaved relatives of patients who died in the hospital did not evaluate the quality of dying better after the introduction of a palliative care nurse champions program on hospital wards, when compared to before [27].…”
Section: Introductionmentioning
confidence: 99%
“…In case of improving palliative care by a palliative care nurse network program, nurse champions firstly require sufficient clinical experience, knowledge of palliative care, teaching capacities, and authority towards managers and colleagues to be a resource and role model for colleagues [24,31]. Some UK studies confirmed that palliative care nurse champions themselves experienced increased knowledge on palliative care, and felt more confident when collaborating with physicians and experts [29][30][31][32]. Subsequently, this should affect the caring behavior of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the United Kingdom reported that nurse champions themselves experienced increased knowledge on palliative care and felt more confident in collaborating with physicians and experts. [4][5][6][7] No study has evaluated the effects on quality of care as experienced by patients or their relatives. In general, experimental studies on quality improvement interventions in EoL care in the hospital are scarce.…”
Section: Introductionmentioning
confidence: 99%